Associations of vitamin D binding protein variants with the vitamin D-induced increase in serum 25-hydroxyvitamin D. (February 2019) - Mehramiz, Mehrane; Khayyatzadeh, Sayyed Saeid; Esmaily, Habibollah; Ghasemi, Faezeh; Sadeghi-Ardekani, Kiana; Tayefi, Maryam; Mirmousavi, Seyed Jamal; Hanachi, Parichehr; Bahrami-Taghanaki, H.; Eslami, Saeed; Vatanparast, Hasan; Ferns, Gordon A.; et al.
Summary: Background: Vitamin D deficiency is a global problem that may be improved by vitamin D supplementation; however, the individual's response to the intervention varies. We aimed to investigate possible genetic factors that may modify the impact of environmental exposure on vitamin D status. The candidate gene variant we investigated was the Gc gene-rs4588 polymorphism at the vitamin D receptor (DBP) locus. Methods: A total of 619 healthy adolescent Iranian girls received 50000 IU of vitamin D3 weekly for 9 weeks. Serum 25(OH) D concentrations, metabolic profiles and dietary intake were measured at baseline and after 9 weeks of supplementation. The genotypes of the DBP variant (rs4588) were analyzed using the TaqMan genotyping assay. Results: Our results revealed that the rs4588 polymorphism might be associated with serum 25-hydroxy vitamin D both at baseline (p value = 0.03) and after intervention (p value = 0.008). It seemed that the outcome of the intervention was gene-related so that the subjects with common AA genotype were a better responder to vitamin D supplementation (Changes (%) 469.5 (427.1) in AA carriers vs. 335.8 (530) in GG holders), and carriers of the less common GG genotype experienced a rise in fasting blood glucose after 9 weeks (Changes (%) 0 (1.5)). Our findings also showed that the statistical interaction between this variant and supplementation was statistically significant (intervention effect p-value<0.001 and p-value SNP effect = 0.03). The regression model also revealed that after adjusted for potential confounders, likelihood of affecting serum 25(OH)D in individuals who were homozygous for the uncommon allele G was less than those homozygous for the more common AA genotype (OR = 4.407 (1.82–8.89); p = 0.001). Conclusion: Serum vitamin 25(OH) D following vitamin 25(OH) D3 supplementation appears to be modified by genetic background. The Gc genetic variant, rs4588 encoding the vitamin D receptor seems to influence the response to vitamin D supplementation.